The Impact of Daily Light Integral from Artificial Lighting on Tomato Seedling Cultivation in Plant Factory - Minggui Zhang; Jiawei Cui; Jun Ju; Youzhi Hu; Xiaojuan Liu; Rui He; Jiali Song; Yanwu Huang; Houcheng Liu (Agronomy)
This study examines the impact of daily light integral (DLI) from artificial lighting on tomato seedlings cultivated in plant factories. By adjusting the light intensity and photoperiod of LED, the research explored the effects of varying DLIs on the morphology, growth, physiological characteristics, photosynthetic pigment content, and chlorophyll fluorescence of tomato seedlings. The optimal DLI enhanced seedling growth, biomass, root vitality, antioxidant enzyme activity, and photosynthetic pigment synthesis. Excessively high DLI or light intensity inhibited photosynthesis, potentially leading to photoinhibition. This study identified the optimal DLI of 13.2 mol·m−2·d−1 through varying DLI gradients in Exp 1 and Exp 2. Based on these findings, Exp 3 established the optimal growth conditions by setting different light intensities and photoperiods under the most suitable DLI, which were a light intensity of 200 μmol·m−2·s−1 and a photoperiod of 18 h. These results provide significant guidance for optimizing the light environment in the cultivation of tomato seedlings in plant factories, helping to improve the light energy utilization efficiency.